Sosialisasi Pemanfaatan Ubi Jalar Ungu Untuk Bahan Utama Puding Ubi Ungu Sebagai Makanan Tambahan Dalam Pencegahan Stunting Bagi Balita di Desa Rancamulya Kecamatan Sumedang Utara: Pengabdian - Alessandra Salsa; Anadza Wafiqotul Azizah; Dinda Aisyarini; Erlangga Agustinus; Ferdi Nata; Liska Virgiawati Aji Rabbani; Muhammad Yahya Ayyasy; Nadzira Nurul Fadhilah; Serevina Nayla Al Zahra; Zahra Devina; Muhammad Fauzi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Stunting remains a major health problem in Indonesia that affects children's physical growth and cognitive development, mainly due to chronic malnutrition from pregnancy to the age of two. This study aims to promote the use of purple sweet potatoes as the main ingredient in pudding as a Supplementary Feeding (PMT) in an effort to prevent stunting among toddlers in Rancamulya Village, North Sumedang District. The method used was a participatory approach involving mothers of toddlers, posyandu cadres, midwives, and nutritionists in the dissemination and training of purple sweet potato pudding making. This activity was carried out in stages, including dissemination of the benefits of purple sweet potatoes, training in pudding processing, and discussions to increase participants' understanding of the importance of consuming nutritious foods. The results of the activity showed an increase in participants' understanding of the benefits of purple sweet potatoes, which are rich in vitamin A, fiber, and antioxidants, as a practical and economical local nutritional solution. This socialization was also supported by previous research showing an improvement in the nutritional status of toddlers who received purple sweet potato-based PMT. Thus, the use of purple sweet potatoes as a supplementary food ingredient can be an effective strategy in reducing the prevalence of stunting in the community.